Novel Perovskite Oxide Hybrid Nanofibers Embedded with Nanocatalysts for Highly Efficient and Durable Electrodes in Direct CO2 Electrolysis - Akhmadjonov, Akromjon; Bae, Kyung Taek; Lee, Kang Taek (Nano-Micro Letters, 2024)
The unique characteristics of nanofibers in rational electrode design enable effective utilization and maximizing material properties for achieving highly efficient and sustainable CO2 reduction reactions (CO2RRs) in solid oxide electrolysis cells (SOECs). However, practical application of nanofiber-based electrodes faces challenges in establishing sufficient interfacial contact and adhesion with the dense electrolyte. To tackle this challenge, a novel hybrid nanofiber electrode, La0.6Sr0.4Co0.15Fe0.8Pd0.05O3−δ (H-LSCFP), is developed by strategically incorporating low aspect ratio crushed LSCFP nanofibers into the excess porous interspace of a high aspect ratio LSCFP nanofiber framework synthesized via electrospinning technique. After consecutive treatment in 100% H2 and CO2 at 700 °C, LSCFP nanofibers form a perovskite phase with in situ exsolved Co metal nanocatalysts and a high concentration of oxygen species on the surface, enhancing CO2 adsorption. The SOEC with the H-LSCFP electrode yielded an outstanding current density of 2.2 A cm−2 in CO2 at 800 °C and 1.5 V, setting a new benchmark among reported nanofiber-based electrodes. Digital twinning of the H-LSCFP reveals improved contact adhesion and increased reaction sites for CO2RR. The present work demonstrates a highly catalytically active and robust nanofiber-based fuel electrode with a hybrid structure, paving the way for further advancements and nanofiber applications in CO2-SOECs. Highlights: 1 The novel hybrid structured nanofiber electrode, incorporating crushed nanofibers into the nanofiber network, is designed to effectively resolve the issue of insufficient interfacial bonding of porous nanofiber electrodes on solid electrolyte interfaces. 2 The hybrid nanofibers are covered with in situ exsolved metal nanocatalysts to enhance CO2 reduction reaction rate. 3 Electrochemical and microstructure 3D reconstruction analyses confirmed the hybrid structure’s efficiency in improving the contact area at the porous-solid interface, leading to an increase in reaction sites.